PENGARUH LATIHAN LONG REPETITIONS FOR PACE JUDGMENT TERHADAP DAYA TAHAN ATLET JARAK MENENGAH PUTRA PASI RIAU - Azhari, Ridwan Azhari; Wijayanti, Ni Putu Nita Wijayanti Nita; ', Slamet (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Form this raisedwas conducted to determine whether there is influence of long repetitions forpacejudgmenteffeck endurance against medium range Pasi men of Riau. Data in this research is the experimental treatment (Experimental), the population in this raised were white athletic athlete riau.Atlet in this raised is6 people.Instrument is done in this research is aimed Balke Test to measure endurance. Then the data is processed with a statistic, to test for normality with Liliefors test at significant level α = 0.05, the hypothesis is there are significant long repetitions for pace judgmenteffeck endurance athletes against medium range riau white men.Based on t test analysis produces tcomputing 47.33 and  ttable 2.015, meaning tcomputing> ttable. Based on the analysis of statistical data, there are an average of Pree-test in 2965 and the average post-test 3180.83, and based on t test after there is a difference calculated numbers increased or increased by an average namely 215.83. From the description above can be concluded there are significant long repetitions forpacejudgment effeck endurance athletes against medium rangeputre  chalky riau. Keywords: long repetitions for pace judgment, results of medium-distance endurance athletes riau white men.